(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Alzheimer's disease (AD) primarily manifests as dementia, cognitive decline, and decline in memory function. The underlying molecular changes include amyloid beta plaque deposition and intracellular neurofibrillary tangles due to phosphorylated tau proteins in the medial temporal lobe. Many people worldwide are affected by AD. So far, successful treatment for AD has not been found to stop or reverse AD progression. Two drugs, namely Donepezil and Memantine, have been found useful to alleviate symptoms of AD, and the quality of life improves in AD patients. However, the medications do not prevent or slow down the disease pathology. Donepezil inhibits acetylcholinesterase enzymatic activity, and Memantine antagonizes NMDA receptors, which in turn increases levels of acetylcholine and helps to regulate glutamate in the brain, respectively. Both drugs are commonly prescribed in AD, but their effectiveness can vary among patients. Clinical studies on Donepezil and Memantine, or in combination, in AD patients have generated conflicting results regarding the overall drug’s safety and effectiveness. Few studies found modest cognitive function improvement, whereas others found little to no benefit. Thus, the present review discusses some of the key aspects relating to the safety and effectiveness of Donepezil and Memantine prescription in AD pathology.